2020
DOI: 10.3389/fmed.2020.570874
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Pulmonary Hypertension Among Maintenance Dialysis Patients With ESRD and Its Associated Factors: A Retrospective Study

Abstract: Aim: To determine the prevalence of pulmonary hypertension (PH) and its associated factors among end-stage renal disease (ESRD) patients who underwent maintenance dialysis.Methods: A total of 491 patients received echocardiography examinations and underwent pulmonary artery systolic pressure (PASP) assessments. A subgroup of 283 patients were subjected to plasma creatinine (Cr) and blood urea nitrogen concentration (BUN) tests, routine blood examinations and electrolyte analysis. First, we compared the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…Kalpana S Mehta et al showed that the prevalence of PH increased as chronic kidney disease stage advanced, and there was a positive correlation between PH and duration of chronic kidney disease, BUN and serum creatinine (23). Zhang et al showed similar results, in which PH was significantly associated with end-stage renal disease, however, the level of BUN and creatinine were not associated with PH (24). Unlike their reports, renal failure was not associated with mortality in PPH patients in our study (Table 6), which might be because the secondary PH caused by renal injury has a completely different mechanism from the renal injury caused by PPH.…”
Section: Discussionmentioning
confidence: 93%
“…Kalpana S Mehta et al showed that the prevalence of PH increased as chronic kidney disease stage advanced, and there was a positive correlation between PH and duration of chronic kidney disease, BUN and serum creatinine (23). Zhang et al showed similar results, in which PH was significantly associated with end-stage renal disease, however, the level of BUN and creatinine were not associated with PH (24). Unlike their reports, renal failure was not associated with mortality in PPH patients in our study (Table 6), which might be because the secondary PH caused by renal injury has a completely different mechanism from the renal injury caused by PPH.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, the toxicity of metabolic wastes contributes to PH following renal failure. Blood components and electrolytes have also been associated with PH, which may be attributed to their roles in vascular remodeling via vascular endothelial cells and vascular smooth muscle cells (Zhang et al, 2016(Zhang et al, , 2020b. The apoptosis-related markers Fas and Fas ligand (FasL) have also been reported to be a higher level in the ESRD patients compared with others (Perianayagam et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary hypertension (PH) has been identified as one of the most common cardiovascular complications associated with various diseases, including cardiovascular diseases and chronic kidney diseases, and particularly in end-stage renal disease ( Barbera et al, 2018 ; Gumus and Saricaoglu, 2020 ; Walther et al, 2020 ; Zhang et al, 2020b ). PH is characterized with a progressive elevation of pulmonary arterial pressure (PAP; Olschewski et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that these studies used different criteria and are not truly equivalent, the majority of them found a greater prevalence of PH in HD patients. 2 , 5 , 6 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…None of the laboratory risk factors like anemia, serum calcium, phosphorus, albumin, PTH, and ferritin were found to be significantly associated with PH which is similar to previous studies. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%